The Significance of Landscape Design in Uzbekistan - Jonuzakov Abduvali Esirgapovich (International Journal on Integrated Education, 2022)
The article discusses a brief history of gardens and parks of the Temurids, the formation of landscape design and the training of in-demand personnel in this area in independent Uzbekistan, the reconstruction of old and the construction of new recreational facilities, etc.